Implementation Of The Learning Model With The 'Ali Method To Improve The Ability To Read The Qur'an Of Students Of The Special Program For Tahfizhul Qur'an (PKTQ) Sukoharjo 2022/2023 State Madrasah Ibtidaiyah - Arrohman, Syauqu Rofiq; Fatimah, Meti; Khasanah, Uswatun (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2022)
The 'Ali method is a way of reading the Qur'an by using keywords, movements, and tartil. This method is straightforward to understand by children, teenagers, and even parents as beginners learning to read the Qur'an. In the process of reading the Qur'an, many students experience difficulties and mistakes, so it is necessary to motivate them to be diligent in reading the Qur'an. It is also necessary to see what factors cause, the need to conduct research in the Special Program Tahfizhul Qur'an (PKTQ) Madrasah Ibtidaiyah Negeri (MIN) 2 Sukoharjo. This research aims to find out how implementing the 'Ali method improves the ability to read the Qur'an in the Special Program for Tahfizhul Qur'an (PKTQ) MIN 2 Sukoharjo. To find out how the implementation of the 'Ali method in PKTQ MIN 2 Sukoharjo improved the ability to read the Qur'an, the author collects theories about the 'Ali method in reading the Qur'an. This research is qualitative by collecting data using interviews, observation, and documentation. To increase the degree of data validity, data validity testing is carried out by extending participation, persistence, observation, triangulation, and using reference materials. The process of analyzing the data is done with three streams, namely: data reduction, data presentation, and verification (conclusion). The research conducted resulted in the final analysis of the implementation of the 'Ali method in improving the ability to read the Qur'an in the Special Program for Tahfizhul Qur'an (PKTQ) MIN 2 Sukoharjo, namely in teaching the teacher is quite good at mastering the material and learning steps with the 'Ali method, although not all teachers are nationally certified. This method is very good because it makes students able to read the Qur'an with the correct makhroj and tajweed quickly. The author can conclude that implementing the 'Ali method in improving the ability to read the Qur'an in the Special Program for Tahfizhul Qur'an (PKTQ) MIN 2 Sukoharjo runs well and correctly and gets maximum results. Keywords: Al Qur'an, Method of 'Ali, PKTQ MIN 2 Sukoharjo